L'épée offerte au dieu Nergal de Ḫubšalum: NABU 1987/76 - Charpin, Dominique
ad H. G. Güterbock, Fs Landsberger, 197-198 and pl. XIII-XV. Inscription is rather aB Mari («Šakkanakku») than aA; gír is to be read namṣarum.